Fresno County Bar Association's Witkin Luncheon with Keynote Speaker Bernard Witkin - Watkins, Howard::::::::: (1982)
Judge Annette LaRue announcing the portrait of late Justice George Hopper to be hung in the Law Library's Hopper Room